2020
DOI: 10.1136/jim-2019-001233
|View full text |Cite
|
Sign up to set email alerts
|

Male Hypogonadism: A Review

Abstract: This article contains a systematic review of the main developments that have occurred in the area of male hypogonadism between the publication of the Endocrine Society Guidelines of 2010 and 2018 and after 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 268 publications
(448 reference statements)
4
13
0
1
Order By: Relevance
“…On the other hand, the majority of firefighters in this cohort were overweight or obese and obesity is the chronic condition associated with the most significant decline in testosterone levels in men. 21,36,37 In our study, as in the general population, a significantly higher BMI was found in…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…On the other hand, the majority of firefighters in this cohort were overweight or obese and obesity is the chronic condition associated with the most significant decline in testosterone levels in men. 21,36,37 In our study, as in the general population, a significantly higher BMI was found in…”
Section: Discussionsupporting
confidence: 69%
“…On the other hand, the majority of firefighters in this cohort were overweight or obese and obesity is the chronic condition associated with the most significant decline in testosterone levels in men. 21,36,37 In our study, as in the general population, a significantly higher BMI was found in Presenting the quartiles, analysis improves external validity of the data, by better reflecting the overall distribution of TT levels among all men of the study population. 6 In contrast, the categorization analysis has the advantage of increasing intragroup specificity by clustering men based on a similar hormonal and/or clinical profile, providing a further description of a multifactorial, complex biological phenomenon.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The diagnosis of hypogonadism was based on the presence of unequivocal low testosterone level, presence of classical hypogonadal symptoms and low/normal serum follicle stimulating hormone (FSH) and luteinizing hormone (LH) levels. In accordance to the Clinical Reference Laboratory of the Center for Disease Control program, biochemical diagnosis of hypogonadism was done in serum testosterone levels lower than 264 ng/dL in patients with hypogonadal symptoms [7,8]. In the present study, patients with hypogonadotropic hypogonadism had normal prolactin levels, normal pituitary and target hormone levels and normal pituitary magnetic resonance imaging.…”
Section: Methodsmentioning
confidence: 72%